Snake and Ladder Games Innovation in Problem based Learning in the Global Warming sub-material SDGs Climate Action Class VII - Margaretha, Nova; Tapilouw, Marisa Christina; Sucahyo, Sucahyo (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The research aims to develop media and test the effectiveness of learning in the form of the snakes and ladders game. The research method used was research and development, research and development methods are used to validate and develop products. This research used a 4D model (define, design, develop and disseminate). The research was carried out in the Even semester of the 2022/2023 academic year at SMP Kristen Satya Wacana. The subjects in this research were 7th grade students at SMP Kristen Satya Wacana. Data was obtained from interviews, questionnaires and tests will be analyzed to obtain valid and reliable data. Testing the effectiveness of using learning media was measured using N-Gain. The results of the learning media validation showed that the value obtained was 87.5% and the material validation results obtained were 79.7% and were declared suitable for use in learning. For the pretest results, students obtained an average score of 76.47, while in the posttest, students obtained an average score of 77.64. Based on the N-Gain test results was 0.05.